Agriculture-related energy consumption, food policy, and CO2 emission reduction: New insights from Pakistan - Raza, Muhammad Yousaf; Zhongpan, Qiu; Pengju, Wang (Frontiers in Environmental Science, 2023)
Fossil fuel energy consumption in the agriculture sector of Pakistan has created serious climate change issues, adding extremely to CO2 emissions, economic growth, and food production. The current research has investigated the most carbon-emitting agriculture factors based on human activities, such as transportation, land, multiple crops, distribution, and consumption under various crops. The study objective is to provide a roadmap for decarbonizing the food supply chain and its current framework toward food policy. The different machines and frameworks applied in agricultural farming can mitigate the CO2 emissions of the agriculture sector if renewable energy technologies (RETs) and renewable energy sources are organized with proper agrarian loads. The major concerns of this paper show a roadmap among a) CO2 emissions in the food supply chain and per capita CO2 emissions, b) food chain activities in the agriculture farming process, c) the agriculture output units and energy consumption, and d) the decarbonization of traditional agriculture and sustainable development in the agriculture sector. The analysis shows that the RETs and mitigation frameworks can lessen the CO2 emissions of farming depending on the type of farm and energy utilization. Finally, the present research highlights possibilities and opportunities for gaining CO2 emissions in crop production linked to Pakistan’s good management practices. In respect to agriculture efficiency and productivity, the government should increase the water, energy, and modern machinery for huge productivity and sustainability. Further policies are provided below.